2017
DOI: 10.1017/s1355617717000315
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functioning in Pedophilia and Child Sexual Offending

Abstract: Our results are the first to demonstrate that executive dysfunctions are related to offense status rather than pedophilic preference. Furthermore, there was evidence for differentiating age and performance correlations between pedophiles and non-pedophiles, which warrants further investigation. (JINS, 2017, 23, 460-470).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 43 publications
2
33
2
Order By: Relevance
“…One explanation for this finding is based on the limitations of the normative comparison data used. It remains unclear how the results from specific executive function tests relate to the complicated processes involved in offending behaviours (Massau et al, 2017). Significant correlations were not seen between executive functioning and older age, depression or substance use scores contrary to our hypothesis, and similar to another investigation (Combalbert et al, 2016).…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…One explanation for this finding is based on the limitations of the normative comparison data used. It remains unclear how the results from specific executive function tests relate to the complicated processes involved in offending behaviours (Massau et al, 2017). Significant correlations were not seen between executive functioning and older age, depression or substance use scores contrary to our hypothesis, and similar to another investigation (Combalbert et al, 2016).…”
Section: Discussioncontrasting
confidence: 95%
“…Executive dysfunction is not inevitable with the presence of a psychiatric condition or substance abuse (Testa & Pantelis, 2009). It remains unclear how the results from specific executive function tests relate to the complicated processes involved in offending behaviours (Massau et al, 2017). A range of other sociodemographic and biopsychosocial factors, and how they contribute to offending, were not addressed in the current study.…”
Section: Discussionmentioning
confidence: 93%
“…Supporting functional magnetic resonance imaging (fMRI) and EEG studies (see below), neuropsychological research has shown executive dysfunctions in child sexual offenders (92). Interestingly, a recent neuropsychological study supports the results by Kärgel et al (91) in so far as executive dysfunctions (worsened response inhibition abilities) are related to offense status rather than pedophilic preference (93).…”
Section: Functional Imaging-functional Magnetic Resonance Imagingmentioning
confidence: 67%
“…Results of fMRI, and neuropsychological studies found impaired (motor) response inhibition functions in sexual offenders against children (90,92). Recent studies revealed that a worsened response inhibition ability is related to offense status rather than pedophilic preference (91,93).…”
Section: Potential Biomarkers For Therapy Response and Risk Assessmentmentioning
confidence: 99%
“…Lastly, all of our patients had a history of sexual offending against children. According to previous research, SOC with PD present reduced inhibitory control compared to men with PD but no offence history (Kärgel et al, 2016;Massau et al, 2017). Thus, impaired inhibitory control might increase the risk of offending, and different levels of impairment might be associated with contact compared to noncontact or no offending.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 92%